Silicon-Solubilizing Media and Its Implication for Characterization of Bacteria to Mitigate Biotic Stress - Bist, Vidisha; Niranjan, Abhishek; Ranjan, Manish; Lehri, Alok; Seem, Karishma; Srivastava, Suchi (Frontiers in Plant Science, 2020)
Silicon (Si), the second most abundant element on earth, remains unavailable for plants’ uptake due to its poor solubility. Microbial interventions to convert it in soluble forms are well documented. However, studies on discrimination of Si and P solubilizing microbes due to common estimation method and sharing of solubilisation mechanism are still obscure. A defined differential media, i.e., silicon solubilizing media (NBRISSM) is developed to screen Si solubilizers. NBRISN13 (B. amyloliquefaciens), a Si solubilizer, exhibiting antagonistic property against Rhizoctonia solani, was further validated for disease resistance. The key finding of the work is that NBRISSM is a novel differential media for screening Si solubilizers, distinct from P solubilizers. Dominance of Pseudomonas and Bacillus spp. for the function of Si solubilization was observed during diversity analysis of Si solubilizers isolated from distinct rhizospheres. Sphingobacterium zeae, a different strain other than Pseudomonas and Bacillus sp, is identified as Si solubilizer along with a novel strain of Pseudomonas sp. Role of acidic phosphatase during Si solubilization has been firstly reported in our study in addition to other pH dependent phenomenon. Study also showed the combinatorial effect of feldspar and NBRISN13 on elicited immune response through (i) increased Si uptake, (ii) reduced disease incidences, (iii) modulation of cell wall degrading and antioxidative enzyme activities, and (iv) induced defense responsive gene expression.